2020
DOI: 10.1002/chem.202000899
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, Synthesis and Evaluation of a Ketol‐Acid Reductoisomerase Inhibitor

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Sa KARI was chosen here because, in contrast to M tKARI, it readily crystallized with a variety of inhibitors [7b,c] . Importantly, the active sites of the two enzymes are virtually identical [12, 15] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sa KARI was chosen here because, in contrast to M tKARI, it readily crystallized with a variety of inhibitors [7b,c] . Importantly, the active sites of the two enzymes are virtually identical [12, 15] .…”
Section: Resultsmentioning
confidence: 99%
“…Sa KARI was expressed and purified as described previously [7c] . Crystals were formed by using the hanging drop method (3 μL drops) in VDX crystallization plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 KARI has also attracted considerable attention as an anti-TB drug target. 12 KARIs are bifunctional enzymes that require Mg 2+ as cofactor in their first half isomerization reaction and NADH or NADPH as reducing agents in the second half reduction reaction. 13 a Previous studies demonstrated that HMKB 3 is the transit intermediate catalysed by the KARI enzyme (EcoKARI) from E. coli ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme is therefore necessary for amino acid prototrophy. Because of its importance in bacteria, plants and fungi, but its absence in metazoans, the enzyme receives increasing attention for the design of antibiotics, herbicides and fungicides [2][3][4]. On the other hand, branched-chain amino acids are valuable compounds for the food, cosmetic and pharmaceutical industries, with a constantly increasing global market (e.g., L-valine: average annual increase rate >5% [5,6]).…”
Section: Introductionmentioning
confidence: 99%